2007
DOI: 10.1111/j.1468-3083.2006.02072.x
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy in patients with thick (= 4 mm) melanoma: a single‐centre experience

Abstract: Our retrospective analysis indicates that the SLN status is predictive of recurrence and survival in patients with thick melanoma, and LM/SLNB should be routinely performed in this subset of melanoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 15 publications
(36 reference statements)
2
19
0
Order By: Relevance
“…In accordance with several other studies focusing on this particular subgroup (table 4), our data clearly confirmed SLNB to be a highly significant prognostic parameter even in high-risk melanoma >4.0 mm [6,7,12,20,21,22,23,24,25,26,27,28]. Despite a relatively low percentage of 29.9% SLN positivity in our cohort, SLN status proved to be highly predictive of a worse prognosis on both RFS as well as OS in uni- and multivariate Cox regression.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In accordance with several other studies focusing on this particular subgroup (table 4), our data clearly confirmed SLNB to be a highly significant prognostic parameter even in high-risk melanoma >4.0 mm [6,7,12,20,21,22,23,24,25,26,27,28]. Despite a relatively low percentage of 29.9% SLN positivity in our cohort, SLN status proved to be highly predictive of a worse prognosis on both RFS as well as OS in uni- and multivariate Cox regression.…”
Section: Discussionsupporting
confidence: 79%
“…Only the cohorts studied by Cecchi et al [24] and Jacobs et al [21] achieved significant results with smaller cohorts of 30–43 patients. Clearly, only larger collectives with a longer follow-up time succeeded in confirming a significantly impaired RFS and OS for SLN status [7,20,23,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This stratification may create some concerns when comparing different studies. We should point out that several authors [4][5][6][7][8][9][10][11][12] stated that sentinel lymph node status predicts DFS as well as OS in patients with thick melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Fairbairn et al achieved similar results in their study. 3 Several other authors [4][5][6][7][8][9][10][11][12] have been successful in correlating the SNB--based staging with improved DFS and OS, advocating its use in this subset of patients. The results presented by Vermeeren et al 13 suggest that the only relevant prognostic factor regarding patients with thick melanoma is SNB and this procedure can be used to stratify patients according to the risk of recurrence.…”
Section: Introductionmentioning
confidence: 99%